Performance optimization of multilink laser powered UAV relay systems - Xuehui Zhao; Yuanchang Zhong; Zhongyuan Mao; Xunzhuo He (Scientific Reports)
Abstract Unmanned Aerial Vehicles (UAVs) can provide flexible wireless connectivity in temporary hotspots and disaster-stricken areas, but their energy constraints remain a challenge. In this paper, we propose a laser-powered UAV relay system where UAVs harvest energy from ground-based laser transmitters and operate in a multi-link shared spectrum environment. With the goal of maximizing the minimum system link throughput, we formulate a joint optimization problem for UAV trajectory and power control and propose an iterative algorithm to efficiently manage energy and mitigate co-channel interference while solving this non-convex problem. Simulation results validate the effectiveness of the proposed scheme and highlight significant performance gains achieved through joint optimization, underscoring the potential of laser-powered UAVs to overcome energy limitations and enhance overall system performance.